Dinamika Perwakafan dalam tinjauan Fikih, Kompilasi Hukum Islam dan Hukum Positif Indonesia - Ma'ruf Hidayat (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Departing from the community's understanding of waqf, it is still traditional that what is called waqf are immovable objects such as land, madrasas, grave lands and others. Whereas in this modern era, community waqf is to produce innovations that are more beneficial for the benefit, both in the economic, social and religious fields. So, this article aims to provide knowledge about the dynamics of waqf in the perspective of fikih scholars and the laws and regulations. The method used by the author to describe this article is search-based. This is done by the author by looking for references related to waqf material either in books or also in book literature. Then the authors look at and read in this article. In addition, the references used cannot be separated from positive legal regulations in Indonesia regarding waqf. The results of this study indicate that waqf in terms of fikih, the legal basis and its implementation in Indonesia have a complementary and mutually reinforcing relationship. From these findings, it can be said that waqf as an instrument of philanthropy has a strong foundation in the view of fikih and positive law in Indonesia in order to provide the public benefit for the community.